Performance on a virtual reality spatial memory navigation task in depressed patients. - Gould NF; Holmes MK; Fantie BD; Luckenbaugh DA; Pine DS; Gould TD; Burgess N; Manji HK; Zarate CA Jr.; Gould, Neda F; Holmes, M Kathleen; Fantie, Bryan D; et al. (American Journal of Psychiatry, 2007)
Objective: Findings on spatial memory in depression have been inconsistent. A navigation task based on virtual reality may provide a more sensitive and consistent measure of the hippocampal-related spatial memory deficits associated with depression.Method: Performance on a novel virtual reality navigation task and a traditional measure of spatial memory was assessed in 30 depressed patients (unipolar and bipolar) and 19 normal comparison subjects.Results: Depressed patients performed significantly worse than comparison subjects on the virtual reality task, as assessed by the number of locations found in the virtual town. Between-group differences were not detected on the traditional measure. The navigation task showed high test-retest reliability.Conclusions: Depressed patients performed worse than healthy subjects on a novel spatial memory task. Virtual reality navigation may provide a consistent, sensitive measure of cognitive deficits in patients with affective disorders, representing a mechanism to study a putative endophenotype for hippocampal function.